Analisis Kinerja Usahatani Cabai Merah Pada Masa Pandemi Covid 19 Di Subak Iseh, Kabupaten Karangasem, Bali - Dewi, Ratna Komala; Artini, Ni Wayan Putu (JURNAL MANAJEMEN AGRIBISNIS, 2023)
This have a look at became conducted to research the factors which might be idea to have an effect on the quantity of purple chili manufacturing and the performance of the pink chili farming in handling production danger and fee risk for the duration of the Covid-19 pandemic. The analytical tool used changed into a simultaneous equation gadget that has structural equation and identity equation, as well as farming analyses. The parameter estimation version become performed the usage of the Eviews 10 pc software. The results confirmed that the quantity of chili manufacturing became encouraged via using labor within the family, the value of fertilizers, the fee of insecticides, and the quantity of efficient bushes together. The input is inelastic. only using labor inside the family and the value of using insecticides have a effective and massive effect on the quantity of chili manufacturing. Farming overall performance become especially low, which is indicated by using the ratio of the acceptance fee to the fee of the variable expenses paid. To growth farmers' profits, farmers need to improve pink chili farming control with the aid of lowering using inputs, particularly using labor within the circle of relatives and insecticides.